What is structural injustice? - Browne, Jude; McKeown, Maeve (New York, USA: Oxford University Press, 2024)
"An abstract is a short description of your longer piece of work and is used as a free layer of content discoverable online. An abstract should not attempt to summarise the whole work as it is also there to show readers whether or not reading further is warranted. It is used to allow people searching on the internet to see that they have encountered a worthwhile 'hit'. This will encourage them to read further by clicking through to the work in full. Keywords are index terms that capture the essence of the topics covered in a piece of work and are essential to improving ranking in search results. Abstracts and Keywords (A&K) combined are used to aid discovery of your content and to generate links across relevant content"--
Keywords: Political Science; Equality